Pengaruh Perceived Value dan Customer Satisfaction Terhadap Revisit Intention di Alinia Farm And Park Resort Dharmasraya - Nanda Amelia; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was carried out against the background of the revisit intention phenomenon which is considered to be caused by perceived value and customer satisfaction factors. This research was conducted with the aim of obtaining information and providing a description of the influence of Perceived Value and Customer Satisfaction on Alinia Farm and Park Resort Dharmasraya. The research is classified as a quantitative descriptive type with the technique for determining the sample, namely through purposive sampling and the number of samples, namely 319 respondents, refers to the Slovin equation. The technique for obtaining research data is with the help of a questionnaire using a Likert scale which has been tested for validation and reliability. The data that has been obtained is analyzed with the help of multiple linear regression analysis using equipment for calculations using SPSS (Statistics Product and Service Solution) version 26.00. Based on the analysis of research results, it was concluded that the results of the t-test showed that the perceived value variable achieved a significant level of 0.021<0.05, which means that there is an influence of the perceived value variable on revisit intention. And the t-test results for the customer satisfaction variable provide a significant level of 0.001<0.05, meaning that there is an influence of the customer satisfaction variable on revisit intention. Based on the results of the f-test, it gives a significant level of 0.001<0.05, showing that the variables perceived value (X1) and customer satisfaction (X2) simultaneously have an influence on revisit intention. The variables perceived value and customer satisfaction have an influence of 4.4%, but the rest is influenced by other variables.